Seismic strengthening of existing RC frame buildings by steel panels - Sezer, Başak. (Thesis (M.S.)-Bogazici University. Kandilli Observatory and Earthquake Research Institute, 2008., 2008)
Every major earthquake in Turkey causes a large number of building suffer moderate damage due to poor construction. If a proper and fast retrofit is not applied, the aftershocks, which may sometimes come days or weeks after the main shock, can push a moderately damaged building into a major damage or even total collapse. Retrofitting these poor constructed buildings using traditional methods may cost a lot of money, labor and time which make the choice of reconstruction better than retrofitting. This research presents a practical retrofit method for moderately damaged buildings, which increases the seismic performance of the structural system by reducing the displacement demand. Fabricated steel panels are used for the retrofit. They are light-weight, easy to handle, and can be constructed very quickly. Moreover, they are cheap, and do not need formwork or skilled workers. They can be designed to compensate for the stiffness and strength degradation, and to fit easily inside a moderately damaged reinforced concrete frame. To test the concept, a half-scale, single-story 3D reinforced concrete frame specimen was constructed at the shake-table laboratories of the Kandilli Observatory and Earthquake Research Institute of Bogazici University, and subjected to recorded real earthquake base accelerations. The amplitudes of base accelerations were increased until a moderate damage level is reached. Then, the damaged RC frames was retrofitted by means of steel panels and tested under the same earthquake. The seismic performance of the specimen before and after the retrofit was evaluated using Turkish seismic code (2007) standards, and the results were compared in terms of stiffness, strength, and deformability. The results have confirmed effectiveness of the proposed retrofit scheme. In order to make this retrofit method easy to comprehend for civil engineers a real structure from Zeytinburnu is chosen to test the panels in computer environment. Performance of the structure evaluated in the same way and effectiveness of the panels have confirmed again.
Keywords: Earthquake resistant design.; Concrete construction -- Earthquake effects.; Plates, Iron and steel.